2018
DOI: 10.21890/ijres.383153
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Levels of Nomophobia Prevalence and Internet Addiction among High School Students: the factors influencing Nomophobia

Abstract: The purpose of this study is to investigate the relationship between nomophobia levels of high school students and their Internet Addiction. This study also investigates the factors including duration of smartphone and mobile Internet use that trigger and create this phenomenon. In order to explore the prevalence of nomophobia among high school students, the survey model was adopted in this study. As part of this survey, 929 high school students were randomly selected among 9th to 12th graders from Turkish hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
46
1
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 36 publications
11
46
1
17
Order By: Relevance
“…The four factors of NMP were assessed and a higher mean was found with factor 3 i.e., not being able to access information with a mean score of 27.5±7.38. Similar findings were seen in studies by Dasgupta et al and Gezgin et al 6,12 Students using cell phones for definite purposes such as sharing pictures, playing games, using cellphones for navigation and online educative material were significantly at a lesser risk for being nomophobic. Students as high as 8 out of 10 responded that cellphones are absolutely necessary in academics.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The four factors of NMP were assessed and a higher mean was found with factor 3 i.e., not being able to access information with a mean score of 27.5±7.38. Similar findings were seen in studies by Dasgupta et al and Gezgin et al 6,12 Students using cell phones for definite purposes such as sharing pictures, playing games, using cellphones for navigation and online educative material were significantly at a lesser risk for being nomophobic. Students as high as 8 out of 10 responded that cellphones are absolutely necessary in academics.…”
Section: Discussionsupporting
confidence: 85%
“…Gezgin et al and Pavithra et al reported no significant association between year of study (grades of study or academic sessions) and nomophobia which was contrary to the finding of our study. 11,12 This could probably be due to more freedom and less vigilance of parents for the grown up kids and also longer duration of usage of cell phones with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…These result are consistent with Gezgin, Cakir, and Yildirim (2018), who found on a sample of high school students that the higher the level of student's internet addiction, the more nomophobic behaviors they tended to exhibit. Another research study links the mediator effect of mindfulness awareness to the relationship between nomophobia and adjustment levels in college students.…”
Section: Discussionsupporting
confidence: 91%
“…For this reason, nomophobia is considered as a modern age phobia that is introduced to our lives as a byproduct of the interaction between people and mobile information and communication technologies, especially smartphones (Yildirim & Correia, 2015, p. 130). The increased use of mobile internet results in increased levels of nomophobia (Gezgin, Cakir, & Yildirim, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%